ANALISIS KERENTANAN PANTAI TIMUR PULAU BINTAN, PROVINSI KEPULAUAN RIAU MENGGUNAKAN DIGITAL SHORELINE ANALYSIS SYSTEM DAN METODE COASTAL VULNERABILITY INDEX - Mario Putra Suhana; I Wayan Nurjaya; Nyoman Metta Natih (Jurnal Teknologi Perikanan dan Kelautan, 2016)
Coastal vulnerability is a condition where there is an increased processes of damage in the coastal areas caused by a variety of factors such as human activity and natural factors such as impact of sea level rise, sea waves and longshore current which cause abrasion and sedimentation processes which is once indicator of pressure on coastal areas even though not always interpreted as the degradation of coastal areas. Coastal vulnerability analysis is very important to be done, by doing a study of the coastal areas condition in particular the study of the vulnerability of a coastal areas will ease in highlighted any sections of a coastal areas which judged having high level of vulnerability and what are the factors that result in the vulnerability of the coastal areas. The research of coastal vulnerability of east coast of Bintan Island was conducted in September-October 2015 with observing physical and oceanographic variables consisting of coastal geomorphology, beach slope, shoreline changes and annual average of sea wave height and tidal range. Coastal vulnerability analysis using coastal vulnerability index (CVI) method by giving a score to each of the variables used in accordance with the categories set by United States Geological Survey (USGS). The results of coastal vulnerability analysis showed coastal geomorphology and beach slope are a variables with a high to very high degree of vulnerability with the vulnerability score of each variables is 4.75 and 5 (score scale range from 1-5). Coastal vulnerability index of east coast of Bintan Island ranged from 3.16-3.54 with an average 3.33 which showed the level of vulnerability of east coast of Bintan Island is in low category.